Semiconductor-biochar composite material as well as preparation method and application thereof
By preparing heterojunction composite materials of TiO2 and ZnO with biochar and combining them with silanized silica, the problems of high recombination rate of photogenerated carriers and easy agglomeration of nanoparticles in traditional photocatalytic materials are solved, achieving efficient photocatalysis and electron transport effects, which are suitable for applications such as wastewater treatment and anaerobic fermentation.
Patent Information
- Application Number
- CN202511254840.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-11-28
AI Technical Summary
In traditional photocatalysis technology, single semiconductor oxide powders have high photogenerated carrier recombination rates and nanoparticles are prone to agglomeration, biochar has a single function as an adsorbent, and mixed materials have low photocatalytic activity.
A semiconductor-biochar composite material is used, which combines TiO2 and ZnO with biochar through a heterojunction. Silanized silica is used to enhance conductivity and optical transparency, forming a Type-II heterojunction to separate photogenerated electron-hole pairs. Semiconductor materials are then loaded using a solvothermal or impregnation method.
It improves photocatalytic activity, enhances light response and electron transport efficiency, and has good structural stability, making it suitable for wastewater treatment and anaerobic fermentation.
Smart Images

Figure CN121016723A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalytic materials technology, specifically relating to a semiconductor-biochar composite material, its preparation method, and its application. Background Technology
[0002] Traditional photocatalysis technologies primarily rely on single semiconductor oxide (such as TiO2) powders to degrade pollutants by generating electron-hole pairs through photoexcitation. However, this approach suffers from problems such as high recombination rates of photogenerated carriers and easy agglomeration of nanoparticles. Biochar has been widely used as an adsorbent or carrier, but traditional techniques often involve single-function materials that rely on physical adsorption and lack catalytically active sites. Hybrid materials obtained by simply mechanically mixing semiconductor oxides and biochar materials exhibit fragmented material properties, low photoelectric effect utilization, and low photocatalytic activity. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a semiconductor-biochar composite material, its preparation method, and its application. The semiconductor-biochar composite material provided by this invention exhibits high photocatalytic activity.
[0004] The present invention provides a semiconductor-biochar composite material, comprising biochar, and a semiconductor material and silanized silica loaded on the surface of the biochar; The semiconductor material includes TiO2 and ZnO; the TiO2 and ZnO form a heterojunction.
[0005] Preferably, the mass ratio of the semiconductor material to biochar is 1:4~12.
[0006] Preferably, the mass ratio of the silanized silica to the semiconductor material is 1:0.7~6.
[0007] Preferably, the mass ratio of TiO2 to ZnO is 1:0.5~2.
[0008] The present invention also provides a method for preparing the semiconductor-biochar composite material described in the above technical solution, including method one or method two, wherein method one includes the following steps: Biomass, semiconductor material precursors and silanized silica are mixed and ground, and the resulting mixture is subjected to a first pyrolysis to obtain a semiconductor-biochar composite material. The second method includes the following steps: Semiconductor materials and silanized silica are loaded onto the surface of biochar using a solvothermal method, impregnation method, or deposition method to obtain semiconductor-biochar composite materials.
[0009] Preferably, the temperature of the first pyrolysis is 700~900℃, and the holding time is 10~12h.
[0010] Preferably, the biomass includes one or more of corn stalks, rice straw, wheat straw, and coconut shells.
[0011] Preferably, the semiconductor material precursor includes a TiO2 precursor and a ZnO precursor. The TiO2 precursor includes tetraisopropyl titanate, tetrabutyl titanate, or titanium tetrachloride. The ZnO precursor includes zinc acetate or zinc nitrate. The mass ratio of the TiO2 precursor to the ZnO precursor is 1:1.
[0012] Preferably, the mass ratio of the semiconductor material precursor to biomass is 1:10; and the mass ratio of the silanized silica to the semiconductor material precursor is 1:2.
[0013] The present invention also provides the application of the semiconductor-biochar composite material described in the above technical solution or the semiconductor-biochar composite material obtained by the above preparation method in promoting anaerobic fermentation, as an electrode material or in wastewater treatment.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a semiconductor-biochar composite material, comprising biochar, and a semiconductor material and silanized silica loaded on the surface of the biochar; the semiconductor material comprises TiO2 and ZnO; the TiO2 and ZnO form a heterojunction.
[0015] The semiconductor-biochar composite material of this invention combines the advantages of photocatalysis (providing additional electron donors through photogenerated electrons) and good conductivity (enhanced by biochar). The built-in electric field of the heterojunction separates charges, and biochar rapidly extracts electrons; the two work synergistically to reduce the electron-hole recombination rate. The semiconductor-biochar composite material maximizes photocatalytic activity and electron transport efficiency through the synergistic effect of heterojunction charge separation and the conductive network of biochar. Simultaneously, the optical transparency, chemical inertness, high specific surface area, and good dispersibility of silanized silica provide additional physical and chemical advantages. The composite material of this invention includes a composite semiconductor material; the energy level matching of ZnO and TiO2 forms a heterojunction (Type-II or Z-type mechanism), promoting the separation of photogenerated electron-hole pairs and reducing recombination. It can simultaneously utilize the strong oxidizing power of TiO2 and the electron migration ability of ZnO to enhance catalytic activity and improve photoresponse. The composite material of the present invention can effectively utilize the photoelectric effect, has high conductivity, large specific surface area and good structural stability, and has significant advantages in expanding the light absorption range, promoting electron transport and improving photoelectric conversion efficiency. It can be used as an electron mediator, reinforcing medium or microbial support.
[0016] This invention also provides a method for preparing the semiconductor-biochar composite material described in the above technical solution, which can be prepared in one or two steps and is simple and easy to implement. The biochar formed by pyrolysis of this invention has richer surface functional groups, a more developed porous structure, and a higher specific surface area.
[0017] This invention utilizes semiconductor materials that can utilize the photoelectric effect and biochar with adsorption and catalytic effects to prepare composite materials. The composite of semiconductor materials and biochar enhances the photoelectric effect and can be applied to fields such as anaerobic fermentation, electrochemical electrode materials, wastewater treatment and environmental remediation. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 The flowcharts for the one-step and two-step methods for preparing semiconductor-biochar composite materials are shown in the examples. Detailed Implementation
[0020] The present invention provides a semiconductor-biochar composite material, comprising biochar, and a semiconductor material and silanized silica loaded on the surface of the biochar; The semiconductor material includes TiO2 and ZnO; the TiO2 and ZnO form a heterojunction.
[0021] In this invention, the specific surface area of the biochar is preferably 200-400 m². 2 / g, specifically 216.3m 2 / g.
[0022] In this invention, the mass ratio of TiO2 to ZnO is preferably 1:0.5~2, more preferably 1:0.65~1.89, and specifically can be 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8 or 1:1.9. The semiconductor material exhibits photoelectric effect.
[0023] In this invention, the mass ratio of the semiconductor material to biochar is preferably 1:4 to 12, specifically 1:4.7 or 1:9.2.
[0024] In this invention, the preferred mass ratio of silanized silica to semiconductor material is 1:0.7~6, specifically 1:2. The silanized silica serves as an auxiliary loading material; its high refractive index and nanoscale particle size induce light scattering, extending the propagation path of incident light within the composite material and improving the light capture efficiency of the semiconductor, particularly significantly enhancing the utilization of ultraviolet-visible light. The transparency of silica (especially in the ultraviolet region) allows light to penetrate its surface directly to the active semiconductor. The insulating properties of silica form a dielectric barrier around the semiconductor particles, inhibiting bulk recombination of photogenerated electron-hole pairs through polarization, creating a complementary effect with the built-in electric field of the heterojunction. The high dispersibility of silanized silica promotes the formation of a continuous conductive network of biochar in the composite material, accelerating electron migration from the semiconductor to the biochar; its chemical inertness prevents semiconductor particles from agglomerating or corroding during the reaction, extending the material's lifespan. Its hydrophilicity (surface hydroxyl groups) improves the dispersibility of the composite material in an aqueous phase, avoiding sedimentation problems caused by the hydrophobicity of biochar. Meanwhile, the high specific surface area and surface silanol groups of silica can adsorb organic pollutants (such as dyes and phenols), enriching them near the active sites of semiconductors, thereby increasing the local reaction concentration and improving the adsorption performance of the complete composite material.
[0025] The present invention also provides a method for preparing the semiconductor-biochar composite material described in the above technical solution, including method one or method two, wherein method one includes the following steps: Biomass, semiconductor material precursors and silanized silica are mixed and ground, and the resulting mixture is subjected to a first pyrolysis to obtain a semiconductor-biochar composite material. The second method includes the following steps: Semiconductor materials and silanized silica are loaded onto the surface of biochar using a solvothermal method, impregnation method, or deposition method to obtain semiconductor-biochar composite materials.
[0026] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.
[0027] Method 1: Mix biomass, semiconductor material precursor and silanized silica and grind them together. Then, perform a first pyrolysis on the resulting mixture to obtain a semiconductor-biochar composite material.
[0028] In this invention, the biomass preferably includes one or more of corn stalks, rice straw, wheat straw, and coconut shells. The biomass is preferably used in powder form, with a particle size preferably of 20-50 mm; the powder is preferably dried before use. The biomass is a raw material for biochar.
[0029] In this invention, the semiconductor material precursor preferably includes a TiO2 precursor and a ZnO precursor. The TiO2 precursor preferably includes tetraisopropyl titanate (TTIP), tetrabutyl titanate, or titanium tetrachloride, specifically tetraisopropyl titanate (TTIP). The ZnO precursor preferably includes zinc acetate (Zn(CH3COO)2) or zinc nitrate, specifically zinc acetate, and the zinc nitrate is preferably Zn(NO3)2·6H2O. The mass ratio of the TiO2 precursor to the ZnO precursor is preferably 1:1.
[0030] In this invention, the preferred mass ratio of the semiconductor material precursor to biomass is 1:10; the preferred mass ratio of the silanized silica to the semiconductor material precursor is 1:2.
[0031] In this invention, the preferred method for preparing silanized silica includes the following steps: surface activation of silica in dilute acid, followed by silanization in a silane coupling agent solution, and solid-liquid separation to obtain silanized silica.
[0032] The silica is preferably silica with a purity greater than 99%. The surface activation process preferably includes washing and drying the silica; the washing is preferably water washing, and the number of washing cycles is preferably 2 to 5, specifically 5; the drying temperature is preferably 105°C, and the drying time is preferably until constant weight is achieved.
[0033] The dilute acid is preferably hydrochloric acid, and the concentration of the hydrochloric acid is preferably 1 mol / L; the surface activation time is preferably 0.5~1 h, specifically 1 h. The surface activation is immersion in dilute acid. The surface activation process preferably includes washing and drying; the washing is preferably water washing, and the number of washings is preferably 5~10 times, specifically 10 times; the drying temperature is preferably 105℃, and the drying time is preferably until constant weight is achieved.
[0034] The volume concentration of the silane coupling agent solution is preferably 1% to 5%, and the solvent of the silane coupling agent solution is preferably water, ethanol, toluene, or isopropanol.
[0035] The silane coupling agent in the silane coupling agent solution preferably includes one or more of KH-550 (γ-aminopropyltriethoxysilane), KH-560 (γ-glycidoxypropyltriethoxysilane), and KH-570 (γ-methacryloyloxytriethoxysilane), specifically KH-550 and KH-560, or KH-550 and KH-570. The mass ratio of KH-550 to KH-560 is preferably 1:1, and the mass ratio of KH-550 to KH-570 is preferably 2:1.
[0036] The liquid-to-solid mass ratio of the silanization treatment is preferably 5-10:1, specifically 10:1. The temperature of the silanization treatment is preferably 30-40℃, specifically 40℃, and the time is preferably 2-4 hours, specifically 4 hours. The silanization treatment involves immersion in a silane coupling agent solution, and the immersion process is preferably accompanied by stirring. The stirring speed is preferably 50-200 r / min, specifically 200 r / min.
[0037] The solid-liquid separation is preferably achieved by filtration or centrifugation; the solid-liquid separation is preferably followed by washing and drying, the washing reagent is preferably ethanol, the number of washings is preferably 3 to 5 times, specifically 5 times; the drying temperature is preferably 105°C, and the drying time is preferably until constant weight is achieved.
[0038] In this invention, a wetting agent is preferably added during the grinding process to improve the uniformity of mixing; the wetting agent is preferably deionized water or ethanol. The grinding speed is preferably 500 r / min, and the grinding time is preferably 1 hour; the grinding is preferably carried out at room temperature. After grinding, the process preferably includes drying to constant weight and sieving (taking the undersize portion); the sieve used for sieving is preferably Φ200*50mm, with a sieve aperture size of 0.180mm and a standard mesh size of 80 mesh.
[0039] In this invention, the preferred temperature for the first pyrolysis is 700~900℃, specifically 900℃, and the preferred holding time is 10~12h, specifically 12h; the preferred heating rate from room temperature to the first pyrolysis temperature is 10~15℃ / min. Taking the precursors tetraisopropyl titanate and zinc acetate as examples, some key reactions during the first pyrolysis process are as follows: Ti(OCH(CH3)3)4→Ti-O-Ti+4(CH3)2CHOH↑, Ti-O-Ti+O2 / H2O→TiO2, Zn(CH3COO)2→ZnO+2CO2↑+CH3COCH3↑, TiO2 + ZnO → TiO2 / ZnO heterojunction Biochar-COOH + TiO2 / ZnO heterojunction → Biochar-COO-Ti-O-Zn + H2O That is, biochar + TiO2 / ZnO → TiO2-ZnO-biochar composite material.
[0040] The biochar obtained from the first pyrolysis has a specific surface area of 200~400 m². 2 / g, TiO2 has a particle size of 10~30 nm, and ZnO has a particle size of 20~50 nm. The TiO2 and ZnO interfaces form a Type-II heterojunction through lattice matching. The porous structure of biochar provides anchoring points for TiO2 and ZnO nanoparticles. At the same time, oxygen-containing functional groups (-OH, -COOH) on the surface of biochar are bonded to TiO2 / ZnO through hydrogen bonds or ester bonds.
[0041] In this invention, the process after the first pyrolysis preferably includes washing the solid obtained from the first pyrolysis and drying it. The washing preferably includes ethanol washing and water washing, the number of ethanol washings is preferably 5 times, and the number of water washings is preferably 5 times; the drying temperature is preferably 105°C, and the drying time is preferably until constant weight is achieved.
[0042] Method 2: Semiconductor materials and silanized silica are loaded onto the surface of biochar using a solvothermal method, impregnation method, or deposition method to obtain a semiconductor-biochar composite material.
[0043] In this invention, the biochar is preferably obtained from biomass through a second pyrolysis, and the biomass preferably includes one or more of corn stalks, rice straw, wheat straw, and coconut shells. The biomass is preferably used in powder form, and the particle size of the powder is preferably 20-50 mm; the powder is preferably dried before use. The temperature of the second pyrolysis is preferably 700-900℃, specifically 900℃, and the holding time is preferably 10-12 hours, specifically 12 hours; the heating rate from room temperature to the second pyrolysis temperature is preferably 10-15℃ / min.
[0044] In this invention, the solvothermal method preferably includes the following steps: Semiconductor precursor solution, silanized silica and biochar were mixed and subjected to a solvothermal reaction, followed by solid-liquid separation to obtain semiconductor-biochar composite material.
[0045] The semiconductor material precursor solution preferably contains TiCl4 and Zn(NO3)2, with a preferred mass ratio of TiCl4 to Zn(NO3)2 of 1:1. The solvent is preferably ethylene glycol and acetylacetone, with a preferred volume ratio of ethylene glycol to acetylacetone of 4-9:1, specifically 4:1. The preferred ratio of semiconductor material precursor to solvent is 1 g:(20-30) mL, specifically 1 g:30 mL.
[0046] The solvothermal reaction temperature is preferably 120~200℃, specifically 160℃, and the time is preferably 6~12h, more preferably 10h. The solvothermal reaction preferably further includes cooling the resulting reaction solution to room temperature. The solid-liquid separation preferably further includes washing the obtained solid and drying. The washing preferably includes ethanol washing and water washing, with the ethanol washing preferably performed 5 times and the water washing preferably performed 5 times; the drying temperature is preferably 105℃, and the drying time is preferably until constant weight is achieved.
[0047] In this invention, the impregnation method preferably includes the following steps: After impregnating silanized silica and biochar in a semiconductor material precursor solution, the two materials are dried and calcined sequentially to obtain a semiconductor-biochar composite material.
[0048] The semiconductor material precursor solution is preferably the same as the semiconductor material precursor solution in the solvothermal method, and will not be described in detail here.
[0049] The impregnation temperature is preferably room temperature, and the time is preferably 2-6 hours, specifically 4 hours. The impregnation is preferably carried out under stirring, and the stirring speed is preferably 50-200 r / min, specifically 200 r / min. The drying temperature is preferably 105℃, and the drying time is preferably until constant weight is achieved.
[0050] The roasting temperature is preferably 300~600℃, specifically 400℃, and the roasting time is preferably 0.5~2h, specifically 1h.
[0051] In this invention, the deposition method preferably includes the following steps: Semiconductor precursor solution, silanized silica and biochar are mixed and then mixed with an alkaline substance to carry out a precipitation reaction. After solid-liquid separation, the resulting solid is calcined to obtain a semiconductor-biochar composite material.
[0052] The semiconductor material precursor solution is preferably the same as the semiconductor material precursor solution in the solvothermal method, and will not be described in detail here.
[0053] The alkaline substance preferably includes one or more of NaOH, Na2CO3, and NaHCO3, specifically NaOH. The amount of alkaline substance added is preferably controlled to maintain the pH of the reaction system at 8-10, specifically 10.
[0054] The precipitation reaction is preferably carried out at a temperature of 40~60℃, specifically 60℃. The precipitation reaction is preferably carried out under stirring, and the stirring speed is preferably 50~200 r / min, specifically 200 r / min.
[0055] The precipitation reaction preferably includes a settling period of 0.5 to 2 hours, specifically 2 hours. The solid-liquid separation preferably includes washing the obtained solid and drying it. The washing is preferably done with water, and the number of washes is preferably 5 to 10 times, specifically 10 times.
[0056] The preferred roasting temperature is 300~600℃, specifically 400℃, and the preferred roasting time is 0.5~2h, specifically 1h.
[0057] The present invention also provides the application of the semiconductor-biochar composite material described in the above technical solution or the semiconductor-biochar composite material obtained by the above preparation method in promoting anaerobic fermentation, as an electrode material or in wastewater treatment.
[0058] In this invention, the light band for stimulating the photoelectric effect of the semiconductor-biochar composite material is preferably 100~400nm, and the photoelectric effect is preferably stimulated by a mercury lamp, an ultraviolet lamp, or a black light lamp.
[0059] To further illustrate the present invention, the semiconductor-biochar composite material, its preparation method, and its application provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.
[0060] Comparative Example 1: Preparation of Biochar Dry corn stalk powder (particle size 20~50mm) was pyrolyzed in a nitrogen atmosphere at a temperature of 900℃ for 12 hours. The heating rate to the pyrolysis temperature was 15℃ / min to obtain corn stalk biochar (yield of about 30%).
[0061] The specific surface area of corn stalk biochar is 216.3 m². 2 / g.
[0062] Comparative Example 2: Preparation of a mixture of TiO2 and ZnO Commercially available TiO2 and ZnO were mechanically mixed at a mass ratio of 1:1 to obtain a mixture of TiO2 and ZnO.
[0063] The TiO2 particles had a diameter of 20 nm, a purity of 99.9%, and a specific surface area of 80 m². 2 / g; ZnO particle size is 20nm, purity is 99.9%, specific surface area is 70m². 2 / g.
[0064] Comparative Example 3: Preparation of a mixture of biochar, TiO2, ZnO and silanized silica Weigh 12g of corn stalk biochar and prepare it using the same method as in Comparative Example 1. Weigh out 6g of a mixture of TiO2 and ZnO, and prepare it in the same way as in Comparative Example 2. Weigh out 3g of silanized silica. The preparation method of silanized silica is as follows: Silane coupling agents KH-550 and KH-560 were selected and mixed in a 1:1 mass ratio. Deionized water was used as the solvent to dissolve the silane coupling agent at a volume concentration of 5%.
[0065] First, the silica was washed with deionized water five times. After washing, it was dried at 105°C to constant weight. The silica was then immersed in dilute acid (1 mol / L hydrochloric acid) for 1 hour for surface activation. After activation, it was washed with deionized water ten times and dried at 105°C to constant weight. The activated and dried silica was then immersed in a silane coupling agent solution with constant temperature stirring. The liquid-to-solid mass ratio was 10:1, the temperature was 40°C, the time was 4 hours, and the stirring speed was 200 r / min. The silanized silica was then filtered, washed five times with anhydrous ethanol, and dried at 105°C to constant weight to obtain silanized silica.
[0066] The mixture of biochar, TiO2 and ZnO, and silanized silica was placed in a ball mill for grinding. During the grinding process, 50 mL of deionized water was added as a wetting agent. The grinding speed was 500 r / min, and the grinding time was 1 h at room temperature. After grinding, the mixture was dried to constant weight and sieved (the sieve used was Φ200*50 mm, sieve aperture size: 0.180 mm, standard mesh number: 80 mesh). The undersize portion was taken to obtain the mixture of biochar, TiO2, ZnO and silanized silica.
[0067] The following Example 1 follows Figure 1 The flowchart shown in the one-step method illustrates the preparation of semiconductor-biochar composite materials: Example 1: One-step preparation of TiO2-ZnO-biochar composite material The preparation method of TiO2-ZnO-biochar composite material is as follows: The semiconductor material precursor includes Zn(CH3COO)2 and tetraisopropyl titanate (TTIP) in a mass ratio of 1:1. The mass ratio of dried corn stalk powder to the semiconductor material precursor is 10:1.
[0068] 60g of dried corn stalk powder (particle size 20~50mm), 3g of Zn(CH3COO)2, 3g of tetraisopropyl titanate (TTIP), and 3g of silanized silica (preparation method same as Comparative Example 3) were mixed and ground (grinding steps same as Comparative Example 3), and then pyrolyzed at a temperature of 900℃ for 12h. The heating rate to the pyrolysis temperature was 15℃ / min. The solid obtained from pyrolysis was washed 5 times with anhydrous ethanol and then 5 times with deionized water. It was then dried in an oven at 105℃ to constant weight to obtain TiO2-ZnO-biochar composite material.
[0069] The following Example 2 follows Figure 1 The flowchart shown in the two-step method (the first step is the preparation of biochar, and the flowchart only illustrates the second step) illustrates the preparation of semiconductor-biochar composite materials: Example 2: Two-step preparation of TiO2-ZnO-biochar composite material 1. The method for preparing corn straw biochar is the same as that for Comparative Example 1.
[0070] 2. Preparation of TiO2-ZnO-biochar composite material: The selected materials were TiCl4, Zn(NO3)2, corn straw biochar, and silanized silica (preparation method is the same as Comparative Example 3). TiO2-ZnO-semiconductor biochar composite material was prepared by solvothermal method.
[0071] 12g of corn stalk biochar, 3g of TiCl4 and 3g of Zn(NO3)2, 3g of silanized silica, 36mL of ethylene glycol and 144mL of acetylacetone were mixed evenly and ground (grinding steps were the same as in Comparative Example 3). Then, a solvothermal reaction was carried out at a temperature of 160℃ for 10h.
[0072] After the solvothermal reaction, the precipitate was washed five times with anhydrous ethanol and then five times with deionized water. It was then dried in an oven at 105°C to constant weight to obtain the TiO2-ZnO (semiconductor)-biochar composite material.
[0073] Application Example 1: Application in Promoting Anaerobic Fermentation The composite material from Example 1 and the materials from Comparative Examples 1-3 were used to promote anaerobic fermentation. The steps were as follows: 1. Add 500g of corn stalk powder, 500g of granular sludge and 15g of the composite material of Example 1 (or the materials of Comparative Examples 1 to 3), and add pure water to a working volume of 5L. Carry out the anaerobic fermentation process at a temperature of 37℃, and set up a control group (without adding the composite material, and the other conditions are the same).
[0074] 2. A mercury lamp was used as the light source to excite the photoelectric effect, employing intermittent illumination for 12 hours followed by a 12-hour interval. The mercury lamp settings were: high-pressure mercury lamp (peak wavelength 365 nm), light intensity: 30~50 mW / cm². 2 (Calibrated at 365nm), Filter: UG-11 (transmits 300~400 nm, cuts off visible light), Distance: 15 cm (with water cooling temperature control).
[0075] 3. Monitor the total biogas production, methane content, carbon dioxide content, and total organic carbon (TOC) content in the liquid phase of anaerobic fermentation for 7 days. Specific results are shown in Table 1 below: Table 1 Results of anaerobic fermentation
[0076] Note: The percentage increase data in Table 1 are all percentage increases or decreases based on Example 1.
[0077] As can be seen from the data in Table 1, the addition of the composite material of the present invention can effectively mediate anaerobic fermentation, improve the methanogenesis rate, and fully degrade organic matter, which helps to obtain clean energy while treating organic waste.
[0078] Application Example 2: Application as an Electrochemical Electrode Material 1. The composite material of Example 1 (or the materials of Comparative Examples 1-3) was uniformly coated onto conductive carbon cloth at a coating amount of 3 mg / cm². 2 (Using PVDF as the binder, the mass ratio of the composite material to the binder is 9:1) After drying at 80℃, a working electrode is prepared. The counter electrode is a bare carbon rod electrode, and the reference electrode is a standard electrode AgCl. A mercury lamp is used as the light source to excite the photoelectric effect, and the light is continuously irradiated for 24 hours.
[0079] 2. Cyclic voltammetry (CV) tests were performed in a three-electrode system using K3[Fe(CN)6] solution as the electrolyte. The scan voltage range was -0.2 V to 0.8 V. The charge transfer resistance of the electrode was measured using electrochemical impedance spectroscopy (EIS). The electrocatalytic water splitting performance of the electrode was tested in 0.1 M Na2SO4 solution. The results are shown in Table 2 below: Table 2 Detection Results of Application Example 2
[0080] As can be seen from the data in Table 2, the composite material has better electrochemical performance, significantly improved conductivity, high intrinsic capacitance, and low charge transport resistance, proving that the composite material of the present invention has excellent charge storage and transport capabilities.
[0081] Application Example 3: Applications that promote wastewater treatment and environmental remediation 1. Prepare simulated polluted water samples Water samples heavily contaminated with semiconductors: prepared with 10 mg / L Pb 2+ Water samples and water samples containing 10 mg / L Cr(VI).
[0082] Organic pollutant water samples: Prepare water samples containing 10 mg / L methylene blue (MB) and 10 mg / L phenol.
[0083] The composite material of Example 2 (or the materials of Comparative Examples 1-3) was added to the water sample at a concentration of 1 g / L, and the sample was shaken in a constant-temperature shaker (150 rpm, 25°C). A mercury lamp was used as the light source to excite the photoelectric effect, and the sample was continuously irradiated for 2, 4, 8, and 24 hours, respectively.
[0084] 2. For water samples heavily contaminated with semiconductors, Pb was detected using atomic absorption spectrometry (AAS) or inductively coupled plasma optical emission spectrometry (ICP-OES). 2+ And Cr(VI) concentration. Organic pollutant water samples: The concentration of methylene blue (MB) or phenol was determined using a UV-Vis spectrophotometer. Adsorption rate and degradation rate were calculated, and the results are shown in Table 3 below: Table 3 Adsorption rate and degradation rate results
[0085] Using the composite material from Example 2, for heavily semiconductor-contaminated water samples, after 2, 4, 8, and 24 hours, Pb... 2+ The concentrations of chromium (Cr) and chromium (VI) decreased to 8.73 mg / L, 7.02 mg / L, 5.47 mg / L, and 3.05 mg / L, respectively, with a degradation rate of 69.5% after 24 hours. The concentrations of Cr (VI) decreased to 9.26 mg / L, 8.84 mg / L, 7.63 mg / L, and 4.49 mg / L, respectively, with a degradation rate of 55.1% after 24 hours. For organic pollutant water samples, after 2, 4, 8, and 24 hours, the concentrations of methylene blue (MB) decreased to 9.00 mg / L, 8.41 mg / L, 7.06 mg / L, and 6.55 mg / L, respectively, with a degradation rate of 34.5% after 24 hours. The concentrations of phenol decreased to 8.76 mg / L, 6.16 mg / L, 4.32 mg / L, and 4.32 mg / L, respectively, with a degradation rate of 56.8% after 24 hours.
[0086] This invention presents a semiconductor-biochar composite material prepared via a one-step or two-step process. Combining the multifunctional properties of semiconductor oxides and biochar, it represents a novel, highly efficient, and versatile material. Biochar, produced from biomass through pyrolysis, possesses a rich porous structure, high specific surface area, and excellent chemical stability, making it an ideal carrier for catalysts or adsorbents. Introducing semiconductor materials such as TiO2 and ZnO, which can excite the photoelectric effect, into biochar not only enhances its catalytic performance but also endows it with photocatalytic and redox activities. In environmental remediation, this composite material effectively decomposes organic pollutants and removes heavy semiconductors; in the energy sector, it exhibits a significant electron transfer promoting effect, improving the efficiency of anaerobic fermentation for methane production; in catalytic reactions, the supported semiconductor particles can efficiently catalyze the cracking of carbon-carbon or carbon-oxygen bonds. Furthermore, the auxiliary material, silica, is further improved in terms of dispersibility and interfacial bonding performance through silanization treatment. This composite material demonstrates broad application potential and represents an important technological exploration for resource recycling and sustainable development.
[0087] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A semiconductor-biochar composite material, characterized in that, Includes biochar, as well as semiconductor materials and silanized silica supported on the surface of the biochar; The semiconductor material includes TiO2 and ZnO; the TiO2 and ZnO form a heterojunction.
2. The semiconductor-biochar composite material according to claim 1, characterized in that, The mass ratio of the semiconductor material to biochar is 1:4~12.
3. The semiconductor-biochar composite material according to claim 1 or 2, characterized in that, The mass ratio of the silanized silica to the semiconductor material is 1:0.7~6.
4. The semiconductor-biochar composite material according to claim 1, characterized in that, The mass ratio of TiO2 to ZnO is 1:0.5~2.
5. The method for preparing the semiconductor-biochar composite material according to any one of claims 1 to 4, characterized in that, This includes either method one or method two, wherein method one includes the following steps: Biomass, semiconductor material precursors and silanized silica are mixed and ground, and the resulting mixture is subjected to a first pyrolysis to obtain a semiconductor-biochar composite material. The second method includes the following steps: Semiconductor materials and silanized silica are loaded onto the surface of biochar using a solvothermal method, impregnation method, or deposition method to obtain semiconductor-biochar composite materials.
6. The preparation method according to claim 5, characterized in that, The temperature of the first pyrolysis is 700~900℃, and the holding time is 10~12h.
7. The preparation method according to claim 5, characterized in that, The biomass includes one or more of corn stalks, rice straw, wheat straw, and coconut shells.
8. The preparation method according to claim 5, characterized in that, The semiconductor material precursor includes a TiO2 precursor and a ZnO precursor. The TiO2 precursor includes tetraisopropyl titanate, tetrabutyl titanate, or titanium tetrachloride. The ZnO precursor includes zinc acetate or zinc nitrate. The mass ratio of the TiO2 precursor to the ZnO precursor is 1:
1.
9. The preparation method according to claim 5, characterized in that, The mass ratio of the semiconductor material precursor to biomass is 1:10; the mass ratio of the silanized silica to the semiconductor material precursor is 1:
2.
10. The application of the semiconductor-biochar composite material according to any one of claims 1 to 4 or the semiconductor-biochar composite material obtained by the preparation method according to any one of claims 5 to 9 in promoting anaerobic fermentation, as an electrode material, or in wastewater treatment.